2022
DOI: 10.3390/children9081246
|View full text |Cite
|
Sign up to set email alerts
|

Positive Parenting Behaviors and Child Development in Ceará, Brazil: A Population-Based Study

Abstract: Parenting practices have been identified as a key determinant of children’s developmental outcomes. The aim of this study was to evaluate the association of parenting practices with child development in a cross-sectional population-based study in a low-income state in northeastern Brazil. The study included data on 3566 caregiver–child pairs, and the children were aged 0–66 months. Positive parenting behaviors (PPBs) were conceptualized in areas of interactive play, social development, and speech and language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…For instance, in a study of 3‐ to 6‐year‐olds from Brazil, higher levels of parent‐reported positive parenting practices (i.e., calculated by subtracting negative parenting practices like inconsistent punishment, neglect, laxness, negative monitoring, and abuse from positive practices like monitoring and moral behavior) related to better performance on behavioral measures of EFs (Luxo Martins et al., 2016). Similar findings were reported in a study of children from birth to 66 months old in Brazil, which found a positive relation between parent‐reported positive parenting behaviors (e.g., positive play, social development, speech, and language interactions) and problem solving (Rocha et al., 2022).…”
Section: Evidence Of Culture Specificity In the Development Of Efs In...supporting
confidence: 86%
“…For instance, in a study of 3‐ to 6‐year‐olds from Brazil, higher levels of parent‐reported positive parenting practices (i.e., calculated by subtracting negative parenting practices like inconsistent punishment, neglect, laxness, negative monitoring, and abuse from positive practices like monitoring and moral behavior) related to better performance on behavioral measures of EFs (Luxo Martins et al., 2016). Similar findings were reported in a study of children from birth to 66 months old in Brazil, which found a positive relation between parent‐reported positive parenting behaviors (e.g., positive play, social development, speech, and language interactions) and problem solving (Rocha et al., 2022).…”
Section: Evidence Of Culture Specificity In the Development Of Efs In...supporting
confidence: 86%
“…Despite scarce data available on interventions to improve child development in early years, (34) some studies have shown that interventions with parents may have a short-term effect of improving ASQ scores. (35) The improvement identi ed at the 6 months visit in the ASQ-3 evaluation scores had possibly led to a relatively lesser concern with the babies and thus less intervention which may explain the impairment identi ed at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…As ações de promoção, prevenção e assistência à saúde da criança implicam o compromisso de gestores públicos em assegurar, por meio de políticas públicas, a qualidade de vida para que a criança alcance seu potencial máximo de crescimento e desenvolvimento. Haja vista que os recentes estudos apontam que fazer esses investimentos contribui para a redução das desigualdades sociais, de enfrentamento à pobreza, favorecendo a construção de uma sociedade mais justa 11 .…”
Section: Discussionunclassified